Biodiversity of Diurnal Birds in City Forest and Teak Forest in Danowudu Village, Ranowulu Subdistrict, Bitung City, North Sulawesi - Iba, Angel; Saroyo, Saroyo; Dapas, Farha (International Journal of Biosystem Research, 2026)
Diurnal birds are widely used as indicators of environmental conditions due to their sensitivity to habitat characteristics. This study analyzed species composition, relative abundance, and diversity of diurnal birds in the City Forest and Teak Forest of Danowudu, Bitung City, North Sulawesi. Data were collected using the line transect method with observations conducted in the morning and afternoon. Species abundance was quantified using the relative abundance index, while species diversity was calculated using the Shannon–Wiener diversity index (H’). A total of 16 species from 12 families with 212 individuals were recorded in the City Forest, resulting in a diversity index (H’) of 2.39, categorized as moderate. In the Teak Forest, 17 species from 12 families with 166 individuals were recorded, with an H’ value of 2.31, also indicating moderate diversity. Pycnonotus aurigaster was the most dominant species in the City Forest, while Rhamphococcyx calyorhynchus showed the highest relative abundance in the Teak Forest. These results demonstrate that both habitats are able to support moderate diurnal bird diversity despite differences in vegetation structure and ongoing anthropogenic pressures.